Ferroelectric properties of (1 - X)Bi(Zn1/2Ti1/2)O3-xPbZrO3ceramics - O. Khamman (2018)
The (1 - x)Bi(Zn1/2Ti1/2)O3-xPbZrO3solid solution ceramics were prepared by using solid-state reaction method, and their ferroelectric properties were investigated. It was found that the perovskite structure is stable for compositions with x ≥ 0.900. Within this composition range, the crystal structure of the solid solution preserves the orthorhombic symmetry of PbZrO3(PZ). The Curie point of the ceramics was found to decrease with increasing Bi(Zn1/2Ti1/2)O3(BZT) content. The intermediate ferroelectric phase of PZ was stabilized by BZT addition and exists within a much wider temperature range in the solid solution. © 2009 Springer Science+Business Media, LLC.